The Nigerian Chronicle - Johnson, Chris (Editor) (Nigerian Chronicle Office, Kumolu House, Shitta Street, Lagos, Southern Nigeria, 1908)
A weekly review of progress in politics, economics, and commerce, and of general news, especially as affecting the two Nigerias.
Keywords: Newspaper; Nigeria